Coefficient stability of operator‐difference schemes with time variable operators - Panayotova, I. N. (Mathematical Modelling and Analysis, 1998)
The problem of the coefficient stability for operator‐ difference schemes with variable operator is investigated. A priori coordinated estimates in the L 2‐norm are obtained for differential‐operator equations and operator‐difference schemes. Estimates in the energy space HA for coefficient stability and stability with respect to the right‐hand side and the initial data are proved under more strong assumptions for operator’s perturbation. First Published Online: 14 Oct 2010